Retained visual function in a subset of patients with long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency (LCHADD). (2nd January 2021) - Dulz, Simon; Atiskova, Yevgeniya; Engel, Peter; Wildner, Jan; Tsiakas, Konstantinos; Santer, Rene
ABSTRACT: Introduction : LCHADD causes retinopathy associated with low vision, visual field defects, nyctalopia and myopia. We report a retrospective long-term single-center study of 6 LCHADD patients trying to clarify if early diagnosis has an impact on the course and outcome of chorioretinal degeneration. Methods : Long-term follow-up of visual acuity and staging of chorioretinal degeneration by fundus photography, optical coherence tomography (OCT) and autofluorescence (AF) in all six patients. Three patients (2 m/1 f; age 8–14.8 years) were diagnosed by newborn screening, a single patient early within the first year of life and treated promptly while the other two (1 m/1 f; age 23–24 years) were diagnosed later after developing symptoms. All carried HADHA variants; five were homozygous for the common p.E510Q variant, in one from the symptomatically diagnosed group p.[E510Q]; [R291*] was detected. Results : All patients showed retinal alterations, but early diagnosis was associated with a milder phenotype and a longer preservation of visual function. Among symptomatic patients, only one showed mild retinal involvement at the time of diagnosis. Conclusion : Despite the small number our study suggests that early diagnosis does not prevent retinopathy but might contribute to a milder phenotype with retained good visual acuity over time. OCT and AF are reliable non-invasive diagnostic tools to estimate the progression of early-stage retinal changes in LCHADD patients.